2017
DOI: 10.1007/s00705-017-3490-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of novel reassortant H5N6-subtype influenza viruses isolated from cats in eastern China

Abstract: Cats are susceptible to influenza A viruses and therefore may act as transmission vectors within households, posing a potential public health concern. Two novel reassortant H5N6 influenza viruses were isolated from cats in Zhejiang Province, Eastern China, in 2016. Both viruses were characterized by whole-genome sequencing with subsequent phylogenetic analysis and genetic comparison. Phylogenetic analysis showed that these viruses received their genes from H5N6, H9N2, and H7N9 influenza viruses isolated from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…H5N6 influenza virus continues to circulate in poultry in Asia and the Pacific region ( OIE World Organisation for Animal Health, 2016 ). Some mammal ( Cao et al, 2017 ; Kim et al, 2017 ) and human cases are also reported occasionally ( Yang et al, 2015 ; Pan et al, 2016 ; Xu W. et al, 2016 ). To investigate the mammal adaption mechanism of H5N6, mouse adaption was conducted ( Peng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…H5N6 influenza virus continues to circulate in poultry in Asia and the Pacific region ( OIE World Organisation for Animal Health, 2016 ). Some mammal ( Cao et al, 2017 ; Kim et al, 2017 ) and human cases are also reported occasionally ( Yang et al, 2015 ; Pan et al, 2016 ; Xu W. et al, 2016 ). To investigate the mammal adaption mechanism of H5N6, mouse adaption was conducted ( Peng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports of occasional influenza cases in cats caused by other IAVs [ 16 , 50 , 51 ]. A recent study confirmed that the presence of antibodies to IAVs of both avian and human origin is not uncommon in European shelter cats [ 6 ].…”
Section: Epidemiology Of Iav Infections In Catsmentioning
confidence: 99%
“…In cats no reassortment between avian and mammalian IAVs was thought to occur until recently, where a novel reassortant of the H5N6-subtype influenza viruses was isolated from two cats in eastern China (90). Both viruses were sequenced and genetic analysis showed that these viruses received their genes from three avian subtypes, including H5N6 (HA, NA, PA), H9N2 (PB2, M, NS), and H7N9 (PB1, NP) influenza subtypes viruses isolated in China (Figure 1).…”
Section: Subtypes Arose From Genetic Reassortmentmentioning
confidence: 99%
“…Analysis of the receptor-binding preference of the feline isolated H5N6 virus revealed that it possesses both avian-and human receptor specificities. Furthermore, the H5N6 virus was able to replicate to high titer in the lungs of infected in mice without prior adaptation, though it was not lethal, indicating mammalian host adaptation (90).…”
Section: Subtypes Arose From Genetic Reassortmentmentioning
confidence: 99%